الرواة العميان في كتاب "الضبط والتبيين لذوي العلل والعاهات من المحدثين" لابن المِبْرَد: جمعا ودراسة - Shumsudin Yabi; Amran Abdul Halim; Mesbahul Hoque; A. Irwan Santeri Doll Kawaid (USIM Press, 2024)
VOL. 6 NO. 2 (2022)